2017
DOI: 10.1089/zeb.2016.1395
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Locomotor Activity in Zebrafish Larvae Using wrMTrck

Abstract: The zebrafish has emerged as a new model system in behavioral neurobiology research. There are numerous assays available to analyze locomotor behavior, but most of these assays require sophisticated equipment and proprietary software. A freely available plugin, wrMTrck, originally developed to analyze locomotor response in Caenorhabditis elegans, has been used in this study to measure locomotion in zebrafish.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Using the wrMTrck software optimized for zebrafish, we inspected the locomotor patterns of the larvae treated with the different test compounds (Fig. 4 ) [ 43 , 44 ]. Visual inspection revealed that the movement patterns of larvae treated with individual compounds such as ISOX, SCOP, and CP were distinguishable from the paths of untreated control larvae (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the wrMTrck software optimized for zebrafish, we inspected the locomotor patterns of the larvae treated with the different test compounds (Fig. 4 ) [ 43 , 44 ]. Visual inspection revealed that the movement patterns of larvae treated with individual compounds such as ISOX, SCOP, and CP were distinguishable from the paths of untreated control larvae (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The settings of wrMTrck, a freely available ImageJ plugin originally developed for examining multiple behavioral parameters in the nematode Caenorhabditis elegans , have been optimized in our lab for zebrafish larvae [ 43 ]. This software was used to study the locomotor patterns of treated larvae and calculate their average speed, distance, and body bend.…”
Section: Methodsmentioning
confidence: 99%
“…wrMTrck is a plugin created by Jesper Søndergaard Pedersen and his team to study how prion-like proteins spread in Caenorhabditis elegans and to analyze locomotor behavior (www.phage.dk/plugins/wrmtrck.html). 17 The plugin installation and setup are very easy, and you can read Selvaraj and Santhakumar 18 for more details. wrMTrck generates raw data, a summary, a video of the tracking analysis, and an image of the path of the animal tracking.…”
Section: Image Processing Algorithmsmentioning
confidence: 99%
“…Laboratories without the Noldus and Maestro Edge can adapt these experiments on similar systems. Alternative cost-effective tracking and electrophysiological systems can be assembled according to Selvaraj and Santhakumar (2017) 35 and Garma et al 17 Zebrafish have multiple outstanding attributes for studies related to human neurological and neurodevelopmental disorders, including conservation of genes with human, and disease-associated phenotypes. The ability to readily perform electrophysiology allows measurements of phenotypes that include seizure propensity after chemical induction.…”
mentioning
confidence: 99%
“…Laboratories without the Noldus and Maestro Edge can adapt these experiments on similar systems. Alternative cost-effective tracking and electrophysiological systems can be assembled according to Selvaraj and Santhakumar (2017) 35 and Garma et al . 17 …”
mentioning
confidence: 99%